The contribution of geothermal power plants to greenhouse gas emission reduction in Indonesia toward the 2030 target - Hudany Wantoko; Muhammad Husen Hatala; Pimpin Hutasoit (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
Indonesia has committed to reducing greenhouse gas emissions by 29%, equivalent to 834 million tons of CO₂, by 2030, with the energy sector expected to contribute 314 million tons of CO₂ reductions. Increasing the share of New and Renewable Energy (NRE), particularly geothermal power plants (PLTP), is a key strategy to achieve this target. As of 2022, the installed geothermal capacity accounts for only 7.8% (2,224.61 MW) of the total estimated potential of 28,500 MW. This study highlights that geothermal power plants generate emissions of approximately 126.2 gCO2e/kWh, which is significantly lower than coal-fired power plants, with emissions of around 1,050 gCO2e/kWh. If the planned geothermal capacity of 5,529 MW is realized by 2030, it could potentially reduce emissions by approximately 23.2 million tons of CO2e annually. However, the current NRE share remains at 11.5%, below the national targets of 23% by 2025 and 31% by 2030. Therefore, accelerating geothermal development is essential, with modular geothermal technology offering a promising solution to support the achievement of Indonesia’s emission reduction targets.